Analisis Efektivitas Penerimaan Retribusi Jasa Umum Atas Pelayanan Persampahan/Kebersihan Di Suku Dinas Lingkungan Hidup Kota Administrasi Jakarta Selatan Tahun 2022 - 2024 - Quinn Winara; Adin Dahuri (Jurnal Ilmu Administrasi Publik, 2026)
This study aims to analyze the effectiveness of general service fee collection for waste management/cleaning services at the Environmental Affairs Sub-Department of South Jakarta Administrative City for the years 2022–2024. Waste Management/Cleaning Service Fees play a crucial part in environmental management for the quality of the environment and public health. This study used a descriptive qualitative method, with data collection through interviews, observations, and documentation. The research findings are based on the Regional Regulation (PERDA) of the Special Capital Region of Jakarta Province No. 1 of 2006 on Regional Fees, which was later revised into No. 3 of 2012 on Regional Fees, further improved with PERDA No. 1 of 2015, and currently uses PERDA No. 1 of 2024 on Regional Taxes and Fees. Fee collection is generally very effective. Revenue realization exceeded targets in 2022 and 2023 and is expected to be effective in 2024. The challenges included a lack of public understanding regarding tariff changes, low levels of compliance, and limited availability of payment facilities. Meanwhile, efforts undertaken included enhancing the digitalization of payment systems, continuous public outreach, and collaboration with various stakeholders. Keywords Effectiveness, Fee Collection, General Service Fees, Waste Management/Cleaning Service Fees, Environmental Affairs Sub-Department of the South Jakarta Administrative City.